An Investigation of Knee Injury Prevalence and Its Mechanism among Iranian Professional Karatekas - Amir Letafatkar; Hamidreza Naserpour (Vesnu Publications, 2021)
Introduction: The knee joint is one of the most frequent points of injuries among karatekas. This study aimed to investigate the prevalence and mechanisms of knee injuries in Iranian professional karatekas.Materials and Methods: 390 kumite-style karatekas who participated in the national team were nominated as subjects in the current study. The sports background information, knee injury profile, and how these injuries affect the subjects' ability and limitation in daily and sports activities were recorded using the Knee Outcome Survey (KOS) questionnaire. Descriptive statistics [95% confidence interval (CI) and standard deviation (SD)] were used to describe the data. In addition, the Pearson correlation test was used to determine the relationship between subscales related to the abilities and limitations in daily and sports activities and their self-reported scores.Results: 73% of karatekas experienced knee injury, which often occurred during training exercises. The cartilage and meniscus injuries (12.5%) and anterior cruciate ligament (ACL) injuries (9.5%) had the highest prevalence, and the predominant mechanism was hitting the opponent with the foot, abrupt rotation, and landing. The correlation coefficient of the subscale of athlete's ability in daily and sports activities with self-reported scores was r = 0.761 (P < 0.001) and r = 0.782 (P < 0.001), respectively. The knee-related quality of life scale in karatekas was also in the range of 95% CI: 21.8-43.0.Conclusion: The present study adds new findings about the knee injury profile of karatekas to the research literature. Therefore, its output can be considered as the input of future studies as a practical factor to prevent injury among karatekas.